In vivo Activity of Silver Nanoparticles Against Pseudomonas aeruginosa Infection in Galleria mellonella - Thomaz, Luciana; Gustavo de Almeida, Luiz; Silva, Flávia R. O.; Cortez, Mauro; Taborda, Carlos P.; Spira, Beny (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is a multidrug-resistant opportunistic pathogen associated with life-threatening nosocomial and community-acquired infections. Antibiotic resistance is an immediate threat to public health and demands an urgent action to discovering new antimicrobial agents. One of the best alternatives for pre-clinical tests with animal models is the greater wax moth Galleria mellonella. Here, we evaluated the antipseudomonal activity of silver nanoparticles (AgNPs) using G. mellonella larvae. The AgNPs were synthesized by a non-toxic biogenic process involving microorganism fermentation. The effect of AgNPs was assessed through characterization and quantification of the hemocytic response, nodulation and phenoloxidase cascade. On average, 80% of the larvae infected with P. aeruginosa and prophylactically treated with nanoparticles survived. Both the specific and total larvae hemocyte counts were restored in the treated group. In addition, the nodulation process and the phenoloxidase cascade were less exacerbated when the larvae were exposed to the silver nanoparticles. We propose that silver nanoparticles protect the larvae from P. aeruginosa infection by directly killing the bacteria and indirectly by preventing an exacerbated immunological response against the pathogen.